As lives no contexto da cibercultura: reflexões a partir de docentes e estudantes da Universidade Federal do Pará campus de Altamira durante a pandemia da Covid 19 - SANTOS, Rose de Jesus (2022)
One of the main measures adopted to reduce the spread of the Coronavirus (SARS-CoV-2), COVID-19, was social distancing. In this context, schools and universities rethought the continuity for the realization of activities, since face-to-face was no longer possible. In this way the lives became popular on the web and became a worldwide phenomenon, because through them classes, debates, scientific events, among others, were held. Therefore, this paper's main goal is to reflect/analyze lives in the context of Higher Education in the year 2020/2021, with a focus on UFPA Altamira (Federal University of Pará, Altamira Campus). The main references were: SANTOS, E; SILVA; CASTELLS, M. The research of qualitative character according to YIN, R. (2016), so it was applied a questionnaire directed to students and interview with 2 faculty members belonging to Youtube channels created and linked to Colleges of UFPA Altamira, the choice focused on identifying the most active in transmissions and among the channels with more followers. A literature review was also carried out aiming at the systematization of works about the popularization of lives. Thus, it can be identified that the lives became a mechanism of communication and interaction, reducing the distance between individuals. The lives gave life to university events and consequently broke the walls of universities, as access to such broadcasts became public.